The debate between electricity and heat, efficacy and safety of irreversible electroporation and radiofrequency ablation in the treatment of liver cancer: A meta-analysis - Xing Rong; Liu Yutong; Liu Yang; Jiang Haihong; Liu Chao; Du Jiru (Open Life Sciences)
Both irreversible electroporation (IRE) and radiofrequency ablation (RFA) are viable ablation methods for localized treatment of liver tumors. We conducted a meta-analysis to access the efficacy and safety of IRE and RFA in liver cancer treatment. Clinical studies on IRE and RFA for the treatment of liver cancer were collected from PubMed and CNKI until June 2023. We screened the literature for ablation success rates at 1 month post-operation, extracting keywords such as “ablation success rate,” “technical success rate,” “recurrence rate,” and “complication” for meta-analysis. A total of 37 articles were included: 24 related to RFA involving 1,685 cases and 13 related to IRE involving 524 cases. The results demonstrate that ablation success rates at post-operative 1 month for IRE and RFA were 86% (95% CI: 82–89%) and 87% (95% CI: 81–92%), respectively. Technical success rates were 96% (95% CI: 88–100%) and 99% (95% CI: 96–100%). In addition, the recurrence rate was 16% (95% CI: 12–22%) in RFA group and 16% (95% CI: 9–23%) in IRE group. In terms of safety, the RFA had a complication rate of 28% (95% CI: 10–50%) and the IRE had a rate of 26% (95% CI: 13–43%). In conclusion, IRE and RFA exhibit similar ablation success rates at 1 month post-operation and comparable complication rates, making them both safe and effective treatment options.